Answer:
m∠EFG =
![161\°](https://img.qammunity.org/2020/formulas/mathematics/high-school/a4jqb9e7o6kb0ufb1w3udz44xr0cziphoi.png)
m∠LMN =
![19\°](https://img.qammunity.org/2020/formulas/mathematics/high-school/vd1jyimthcdawp26hnmpnu7g1c1kyksane.png)
Explanation:
Given:
∠EFG and ∠LMN are supplementary angles
m∠EFG =
![(3x + 17)\°](https://img.qammunity.org/2020/formulas/mathematics/high-school/v3j5udyc7798h4oskcyuj515kvia2wga8w.png)
m∠LMN =
![((1)/(2)x - 5)\°](https://img.qammunity.org/2020/formulas/mathematics/high-school/92dlndvrcvhluon562ijbhmm4dp3n1wyqk.png)
We need to find m∠EFG and m∠LMN
Now we know that sum of the Supplementary angles are 180°
Hence we can say that;
m∠EFG + m∠LMN = 180°
Substituting the given values we get;
![(3x + 17)+ ((1)/(2)x - 5) = 180\\\\3x+17+(1)/(2)x-5 =180\\\\3x+(1)/(2)x-12=180\\\\3x+(1)/(2)x=180-12\\\\(3x*2)/(2)+(1)/(2)x = 168\\\\(6x+x)/(2) = 168\\\\7x = 168*2\\\\7x = 336\\\\x=(336)/(7)= 48](https://img.qammunity.org/2020/formulas/mathematics/high-school/nwkjpl7hzoyfr8skx0a07ca8um96h3y0fb.png)
Now Substituting the value of x to find the measures of angle;
m∠EFG =
![(3x + 17)\° = (3*48+17)\°= (144+17)\° =161\°](https://img.qammunity.org/2020/formulas/mathematics/high-school/twypjnohlhgkwyyccaezn3fjypzzg1qksl.png)
m∠LMN =
![((1)/(2)x - 5)\°=((1)/(2)* 48 - 5)\°= (24 - 5)\°=19\°](https://img.qammunity.org/2020/formulas/mathematics/high-school/2h8p8a6xv7xv3m9ffvpv6w994a7vzzzpio.png)